Developing a behaviour rubric for the practical model of ethical behaviour for clinical nursing - Yuriko Tsujio; Mio Yasuda; Mikage Hattori; Tomoko Yoshioka; Naomi Nakamura; Mitsuko Nakata; Satoshi Teramukai; Yuichi Minemura; Tomomi Azuma (Wiley, 2023)
Abstract Aim The present study aimed to develop an ethical behaviour rubric for nurses and evaluate its reliability and validity. Method This study was to designed to construct a rubric and evaluate the reliability and validity. The ethical behaviour rubric was distributed to 241 nurses and 154 were completed and returned. The intra‐rater and inter‐rater reliability were evaluated by intraclass correlation coefficient (ICC) for all 10 items on the ethical behaviour rubric, and the internal consistency reliability was evaluated using Cronbach's α. Construct validity was tested with explanatory factor analysis, and criterion validity was tested using the known‐groups method. Results Intra‐rater reliability had a high interrater agreement (ICC = 0.9), and inter‐rater reliability had a high interrater agreement (ICC = 0.84). The Cronbach's α coefficient was 0.96. There was a linear correlation between the number of years of nursing experience and rubric scores p < 0.001. Exploratory factor analysis revealed 10 items loading on four factors. The result of factor analysis is that Cronbach's α was 0.93 for the first factor, 0.83 for the second factor, 0.91 for the third factor, and 0.77 for the fourth factor. Conclusions Our rubric was found to be a valid and reliable tool for the assessment of ethical behaviour among nurses in Japan.